Endometriosis-related pelvic pain following laparoscopic surgical treatment. Issue 3 (September 2020) - Harris, Amani; McCaughey, Tristan; Tsaltas, Jim; Davies-Tuck, Miranda; Ratner, Roni; Najjar, Haider; Barel, Oshri
Introduction: Endometriosis is a common, often-debilitating disease, affecting women of reproductive age. Pain is a common symptom of the disease and is commonly treated by surgery, medical therapy, or a combination of the two. This study aimed to evaluate the rates of ongoing pain post laparoscopic excision and the risk factors for ongoing pain symptoms. Methods: This retrospective cohort study analyzed the medical records of all patients who underwent laparoscopic surgery for endometriosis in a large tertiary healthcare service in Australia between January 2009 and September 2016. Results were analyzed using SPSS statistics version 11. Results: A total of 972 patients met the inclusion criteria; of these, 398 had follow-up at our hospital network and were included in the final analysis. The median age was 34.5 years, 69.6% were of Caucasian ethnicity, and the median body mass index was 25.9; 70.6% of our patients reported decreased pain after surgery. Patients who suffered from chronic pain were twice as likely to experience ongoing pain, while patients with stage 3–4 endometriosis were found to have 65% reduced odds of pain at follow-up (95% confidence interval = 0.22–0.61, p < 0.001). In univariate analysis of non-Caucasian patients, those who had a specialist endometriosis surgeon perform the surgery had significantly higher incidence of symptom improvement (58% reduced odds of recurrent pain and 40% reduced odds, p < 0.05, accordingly). Conclusion: The prevalence and severity of pain associated with endometriosis mandates a thorough understanding of the effectiveness of current management. Our article highlights the utility of laparoscopic surgery in treating endometriosis-associated pain.